Pembuatan Aplikasi Sensus Penduduk Untuk Desa Wulunggunung - Teguh Hananto Widodo; Oky Dwi Nurhayati; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
Population is all of the people who lives in an area for more and less than 6 month, but aim to live in there for a long time. It require an accurate data regarding aspects of quantity and quality of the population to get a picture about condition of population in certain area.The level of accuracy of the data obtained strongly influence the accuracy of the analysis and prediction of demographic conditions. Because of development of technology rapidly, the census is a proses of recording, calculation and publication of demographic data which carried out on all the permanent residents who lived in a particular region or country simultaneouslycarried out with the census application to be a storage for a valid data. This application can make a census population easier to create report and save a valid data of a particular region. This application is built using Delphi. Applications census contains personal data of an area that the scope of development is still in the village scale. This application is Expected to be of little help in making a report and other purposes.